2012
DOI: 10.1021/bi300151q
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Intermediate Semiquinone with Surrounding Protein Residues at the QH Site of Wild-Type and D75H Mutant Cytochrome bo3 from Escherichia coli

Abstract: Selective 15N isotope labeling of the cytochrome bo3 ubiquinol oxidase from E. coli with auxotrophs was used to characterize the hyperfine couplings with the side-chain nitrogens from R71, H98, and Q101 residues and peptide nitrogens from R71 and H98 residues around the semiquinone (SQ) at the high-affinity QH site. The 2D ESEEM (HYSCORE) data have directly identified the Nε of R71 as an H-bond donor carrying the largest amount of the unpaired spin density. In addition, weaker hyperfine couplings with the side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(80 citation statements)
references
References 41 publications
4
76
0
Order By: Relevance
“…[10,11,29,66] This observation has been discussed with regard to the quinone electron transfer role as one-electron (Q A ,A 1 , and Q H )o rt wo-electron transfer agent (Q B ,q uinonesi nv itro) coupledt ot he binding or releaseo ft wo protons. [44] Whereas the number of studied systemsi st oo low for substantial conclusions, the present study providesa nu nprecedented example of aq uinone with an extremelyh igh asymmetrics pin density distribution for the MSK D intermediate whereas menaquinols in the Q D site are in dynamic equilibrium with the quinone pool and bind to release two electrons and two protons before unbinding in the oxidized menaquinone form. It can therefore be concluded that the production within aQsite of ah ighly asymmetrics pin density distribution for the SQ intermediate does not systematically translate into ar ole as ao neelectron transfer agent forthis Qs ite.…”
Section: H/mentioning
confidence: 78%
See 2 more Smart Citations
“…[10,11,29,66] This observation has been discussed with regard to the quinone electron transfer role as one-electron (Q A ,A 1 , and Q H )o rt wo-electron transfer agent (Q B ,q uinonesi nv itro) coupledt ot he binding or releaseo ft wo protons. [44] Whereas the number of studied systemsi st oo low for substantial conclusions, the present study providesa nu nprecedented example of aq uinone with an extremelyh igh asymmetrics pin density distribution for the MSK D intermediate whereas menaquinols in the Q D site are in dynamic equilibrium with the quinone pool and bind to release two electrons and two protons before unbinding in the oxidized menaquinone form. It can therefore be concluded that the production within aQsite of ah ighly asymmetrics pin density distribution for the SQ intermediate does not systematically translate into ar ole as ao neelectron transfer agent forthis Qs ite.…”
Section: H/mentioning
confidence: 78%
“…[40][41][42] With this strategy,s electively 15 N-labeled cyt bo 3 samples from E. coli were used in 15 NH YSCORE experiments to identify the amino acids interacting with the stabilized ubisemiquinone species bounda tt he high affinity quinone binding site (Q H )o ft he wild-type enzymeo ri naQ-site mutant. [43,44] Ar everse labelinga pproachi nw hich this enzyme was uniformly 15 N-labeled except for selected amino acid types has also been used. [44] In this work, 2 Ha nd 15 Ni nvivo selective labelingi su sed to resolve quinone-protein interactions in the respiratory nitrate reductase (Nar) from E. coli,awidely distributed prokaryotic enzyme that allows anaerobic respiration with nitrate as at erminal electron acceptor.T his membrane-bound heterotrimeric complex( NarGHI) couplest he oxidation of membrane quinols at ap eriplasmically oriented Qs ite to the cytoplasmic twoelectron reduction of nitrate into nitrite.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the strongly H-bonded protons H1 and H2 are on the O 1 side of the SQ H , however, their assignment to residues D75 and R71 is ambiguous. 18,20 Parallel MD runs were set up with proton H1 being assigned either to the β-carboxyl of D75 or to the N ε of R71 to test both possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…25 However, the DFT calculations utilizing different simplified models of either the ubiquinone anion-radical or neutral radical H-bonding failed to reproduce all experimentally determined 1 H (H-bonds, 5′-methyl), 13 C (carbonyls), and 14 N (nitrogen H-bond donors) couplings simultaneously. 20,2830 Hence, the SQ H protonation state, as well as the general hydrogen bond network, remain uncertain. What is required to clarify the situation is a more precise, experimentally characterized model of the SQ H binding in cyt bo 3 including the orientations of the H-bonds and the corresponding donor for each strongly coupled proton.…”
mentioning
confidence: 99%